Effects of using EM juice supplemented within feed of tadpole frog nursing - Kandee, Thanousinh; Tayamad, Khambou; Singpa, Bounlam; Chanthakoun , Vongphasith; Meekhen, Sith (Souphanouvong University Journal Multidisciplinary Research and Development, 2016)
This experiment was conducted to determine the effects of feed and efficiency microorganism (EM) juice on growth performance of Tadpole nursery. A 2*2 factorial in completely randomized design was used in this study. Factor 1 was feed (completed feed (IF) and mix feed, MF)) and factor 2 was EM juice (no supplemented and supplemented). Frog tadpole at 10 days of age, an average body weight at 0.008 g/tadpole and rearing at 3,035 tadpole/m2 in the net cage during 4 weeks and fed 3 time per day with 10 % of total body weight of tadpole. The results show that both completed feed and mix feed had significantly different (p<0.001) in ADG, FCR, were higher in IF than MF, survival rate was not significantly (P>0.05) among IF and MF. For EM juice supplemented was showed that not significantly different (p>0.05) in ADG, FCR. However, the survival rate was significantly different (P<0.001) when compare among tadpole fed with no EM and EM supplemented. The efficiency of economic return was showed higher in tadpole fed with EM supplemented. In conclusion, the tadpole nursing with completed feed within EM juice supplemented was higher efficiency of growth performance, feed utilization, survival rate and economic return efficiency than tadpole fed with no EM supplemented.